2000
DOI: 10.2337/diabetes.49.6.918
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to exogenous insulin promotes IgG1 and the T-helper 2-associated IgG4 responses to insulin but not to other islet autoantigens.

Abstract: Insulin immunization in animal models induces T-h e l p e r (Th) 2-like antibody subclass responses to insulin and other -cell antigens. The aim of this study was to d e t e rmine whether exposure to insulin in humans resulted in a similar subclass bias of the humoral immune response. Levels of IgG subclass antibodies to insulin (IAs), GAD, and IA-2 were measured before and after treatment w i t h insulin in the following groups of patients: 29 patients with newly diagnosed type 1 diabetes treated with intrave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 30 publications
4
35
0
Order By: Relevance
“…This observation is in agreement with a previous study which showed that oral insulin administration is associated with lower levels of IgG1-IA after 3 months of treatment [15]. Conversely, subcutaneous insulin administration has been shown to induce high levels of IgG1-IA and a Th2-associated IgG4 response against insulin after 12 months of treatment [21].…”
Section: Discussionsupporting
confidence: 93%
“…This observation is in agreement with a previous study which showed that oral insulin administration is associated with lower levels of IgG1-IA after 3 months of treatment [15]. Conversely, subcutaneous insulin administration has been shown to induce high levels of IgG1-IA and a Th2-associated IgG4 response against insulin after 12 months of treatment [21].…”
Section: Discussionsupporting
confidence: 93%
“…The administration of intranasal insulin has not been observed to affect first-phase insulin response and the levels of GAD65Ab in autoantibody-positive subjects at risk for T1D (35). Similarly, the initiation of exogenous insulin treatment in patients with newly diagnosed T1D has not been observed to induce any isotype-specific responses to GAD65 although induction of an Ig4 response to insulin was observed (36). This indicates that intranasal insulin treatment hardly had any impact on the present observations, and consistently, no immediate change was observed in isotype-or epitope-specific responses after the initiation of the intervention trial in the present study.…”
Section: Discussionmentioning
confidence: 88%
“…It has been reported that insulin immunization in animal models drives a Th2 dominated phenotype and induces Th2-like antibody subclass responses to insulin [58]. Antigen induction of a Th2 regulatory response may also occur in man as illustrated in a recent study which reported that the antibody subclass of the insulin autoantibodies in insulin-treated patients was consistent with enhancement of Th2 autoimmunity [65].…”
Section: Immunologic Vaccinationmentioning
confidence: 57%